Peningkatan Kapasitas Usaha Kue Kering Ibu Rumah Tangga Melalui Pelatihan Keberlanjutan Usaha di Depok - Ika Agustina; Sukardi, Sukardi; Asep Surya Lesmana; Tohiroh, Tohiroh; Siti Mulasih (Yayasan Literasi Sains Indonesia, 2025)
This training program was designed to enhance business management competencies among housewives engaged in small-scale pastry enterprises in Pondok Petir, Bojongsari, Depok. The initiative specifically addressed key challenges, including financial management, task allocation among group members, and the development of effective marketing strategies. Structured to support the sustainability and growth of these micro-enterprises, the curriculum provided practical frameworks for financial oversight, product innovation, and digital marketing implementation. Furthermore, the program sought to empower participants by equipping them with strategies to scale their operations, refine product quality, and broaden market penetration.Educational methodologies emphasized participatory learning, applied simulations, and case study analyses to ensure the direct applicability of acquired skills in real-world contexts. A collaborative group-based approach was implemented to strengthen interpersonal solidarity and cooperative dynamics, thereby optimizing collective productivity.The three-month training program, conducted from January to March 2025, adopted a phased and needs-oriented structure to align with participants’ practical requirements. Post-intervention evaluations demonstrated that the training significantly improved participants’ business management proficiency, operational efficiency, and market reach. These outcomes underscore the efficacy of group-based educational interventions in fostering entrepreneurial development within community-driven enterprises.